Comorbidities associated with dysphagia after acute ischemic stroke - Anel Karisik; Vincent Bader; Kurt Moelgg; Lucie Buergi; Benjamin Dejakum; Silvia Komarek; Michael Thomas Eller; Thomas Toell; Lukas Mayer-Suess; Raimund Pechlaner; Julian Granna; Simon Sollereder; et al. (BMC Neurology, 2024)
Abstract Background Pre-existing comorbidities increase the likelihood of post-stroke dysphagia. This study investigates comorbidity prevalence in patients with dysphagia after ischemic stroke. Methods The data of patients with acute ischemic stroke from two large representative cohorts (STROKE-CARD trial 2014–2019 and STROKE-CARD registry 2020–2022 – both study center Innsbruck, Austria) were analyzed for the presence of dysphagia at hospital admission (clinical swallowing examination). Comorbidities were assessed using the Charlson Comorbidity Index (CCI). Results Of 2054 patients with ischemic stroke, 17.2% showed dysphagia at hospital admission. Patients with dysphagia were older (77.8 ± 11.9 vs. 73.6 ± 14.3 years, p < 0.001), had more severe strokes (NIHSS 7(4–12) vs. 2(1–4), p < 0.001) and had higher CCI scores (4.7 ± 2.1 vs. 3.8 ± 2.0, p < 0.001) than those without swallowing impairment. Dysphagia correlated with hypertension (p = 0.034), atrial fibrillation (p < 0.001), diabetes (p = 0.002), non-smoking status (p = 0.014), myocardial infarction (p = 0.002), heart failure (p = 0.002), peripheral arterial disease (p < 0.001), severe chronic liver disease (p = 0.002) and kidney disease (p = 0.010). After adjusting for relevant factors, the associations with dysphagia remained significant for diabetes (p = 0.005), peripheral arterial disease (p = 0.007), kidney disease (p = 0.014), liver disease (p = 0.003) and overall CCI (p < 0.001). Conclusions Patients with multiple comorbidities have a higher risk of developing post-stroke dysphagia. Therefore, early and thorough screening for swallowing impairment after acute ischemic stroke is crucial especially in those with multiple concomitant diseases. Trial registration Stroke Card Registry (NCT04582825), Stroke Card Trial (NCT02156778).